Substituent effect on TADF properties of 2-modified 4,6-bis(3,6-di-tert-butyl-9-carbazolyl)-5-methylpyrimidines - Fiodorova, Irina; Serevičius, Tomas; Skaisgiris, Rokas; Juršėnas, Saulius; Tumkevicius, Sigitas (Beilstein Journal of Organic Chemistry, 2022)
The interest in organic materials exhibiting thermally activated delayed fluorescence (TADF) significantly increased in recent years owing to their potential application as emitters in highly efficient organic light emitting diodes (OLEDs). Simple modification of the molecular structure of TADF compounds through the selection of different electron-donating or accepting fragments opens great possibilities to tune the emission properties and rates. Here we present the synthesis of a series of novel pyrimidine–carbazole emitters and their photophysical characterization in view of effects of substituents in the pyrimidine ring on their TADF properties. We demonstrate that electron-withdrawing substituents directly connected to the pyrimidine unit have greater impact on the lowering of the energy gap between singlet and triplet states (ΔEST) for efficient TADF as compared to those attached through a phenylene bridge. A modification of the pyrimidine unit with CN, SCH3, and SO2CH3 functional groups at position 2 is shown to enhance the emission yield up to 0.5 with pronounced TADF activity.
Keywords: carbazole; pyrimidine; RTP; synthesis; thermally activated delayed fluorescence

(untitled) - Uoyama, H.; Goushi, K.; Shizu, K.; Nomura, H.; Adachi, C. (Nature, 2012)

(untitled) - Endo, A.; Sato, K.; Yoshimura, K.; Kai, T.; Kawada, A.; Miyazaki, H.; Adachi, C. (Appl. Phys. Lett., 2011)

(untitled) - Xie, F.-M.; Zhou, J.-X.; Li, Y.-Q.; Tang, J.-X. (J. Mater. Chem. C, 2020)

(untitled) - Wong, M. Y.; Zysman-Colman, E. (Adv. Mater. (Weinheim, Ger.), 2017)

(untitled) - Dias, F. B.; Penfold, T. J.; Monkman, A. P. (Methods Appl. Fluoresc., 2017)

(untitled) - Tao, Y.; Yuan, K.; Chen, T.; Xu, P.; Li, H.; Chen, R.; Zheng, C.; Zhang, L.; Huang, W. (Adv. Mater. (Weinheim, Ger.), 2014)

(untitled) - Yang, Z.; Mao, Z.; Xie, Z.; Zhang, Y.; Liu, S.; Zhao, J.; Xu, J.; Chi, Z.; Aldred, M. P. (Chem. Soc. Rev., 2017)

(untitled) - Cai, X.; Su, S.-J. (Adv. Funct. Mater., 2018)

(untitled) - Komatsu, R.; Sasabe, H.; Kido, J. (J. Photonics Energy, 2018)

(untitled) - Lee, C. H.; Choi, S. H.; Oh, S. J.; Lee, J. H.; Shim, J. W.; Adachi, C.; Lee, S. Y. (RSC Adv., 2020)

(untitled) - Yu, L.; Yang, C. (J. Mater. Chem. C, 2021)

(untitled) - Lin, L.-Y.; Tsai, C.-H.; Wong, K.-T.; Huang, T.-W.; Wu, C.-C.; Chou, S.-H.; Lin, F.; Chen, S.-H.; Tsai, A.-I. (J. Mater. Chem., 2011)

(untitled) - Chiu, S.-W.; Lin, L.-Y.; Lin, H.-W.; Chen, Y.-H.; Huang, Z.-Y.; Lin, Y.-T.; Lin, F.; Liu, Y.-H.; Wong, K.-T. (Chem. Commun., 2012)

(untitled) - Wu, C.-H.; Pan, T.-Y.; Hong, S.-H.; Wang, C.-L.; Kuo, H.-H.; Chu, Y.-Y.; Diau, E. W.-G.; Lin, C.-Y. (Chem. Commun., 2012)

(untitled) - Ortiz, R. P.; Casado, J.; Hernández, V.; López Navarrete, J. T.; Letizia, J. A.; Ratner, M. A.; Facchetti, A.; Marks, T. J. (Chem. – Eur. J., 2009)

(untitled) - Irfan, A.; Al-Sehemi, A. G.; Al-Assiri, M. S. (J. Mol. Graphics Modell., 2013)

(untitled) - Kojima, T.; Nishida, J.-i.; Tokito, S.; Yamashita, Y. (Chem. Lett., 2009)

(untitled) - Achelle, S.; Nouira, I.; Pfaffinger, B.; Ramondenc, Y.; Plé, N.; Rodríguez-López, J. (J. Org. Chem., 2009)

(untitled) - Cvejn, D.; Achelle, S.; Pytela, O.; Malval, J.-P.; Spangenberg, A.; Cabon, N.; Bureš, F.; Robin-le Guen, F. (Dyes Pigm., 2016)

(untitled) - Tang, R.; Wang, X.; Zhang, W.; Zhuang, X.; Bi, S.; Zhang, W.; Zhang, F. (J. Mater. Chem. C, 2016)

(untitled) - Achelle, S.; Rodríguez‐López, J.; Bureš, F.; Robin‐le Guen, F. (Chem. Rec., 2020)

(untitled) - Verbitskiy, E. V.; Dinastiya, E. M.; Baranova, A. A.; Khokhlov, K. O.; Chuvashov, R. D.; Yakovleva, Y. A.; Makarova, N. I.; Vetrova, E. V.; Metelitsa, A. V.; Slepukhin, P. A.; Rusinov, G. L.; Chupakhin, O. N.; et al. (Dyes Pigm., 2018)

(untitled) - Boländer, A.; Kieser, D.; Voss, C.; Bauer, S.; Schön, C.; Burgold, S.; Bittner, T.; Hölzer, J.; Heyny-von Haußen, R.; Mall, G.; Goetschy, V.; Czech, C.; et al. (J. Med. Chem., 2012)

(untitled) - Achelle, S.; Hodée, M.; Massue, J.; Fihey, A.; Katan, C. (Dyes Pigm., 2022)

(untitled) - Komatsu, R.; Sasabe, H.; Seino, Y.; Nakao, K.; Kido, J. (J. Mater. Chem. C, 2016)

(untitled) - Xiang, Y.; Zhao, Y.; Xu, N.; Gong, S.; Ni, F.; Wu, K.; Luo, J.; Xie, G.; Lu, Z.-H.; Yang, C. (J. Mater. Chem. C, 2017)

(untitled) - Xiang, Y.; Li, P.; Gong, S.; Huang, Y.-H.; Wang, C.-Y.; Zhong, C.; Zeng, W.; Chen, Z.; Lee, W.-K.; Yin, X.; Wu, C.-C.; Yang, C. (Sci. Adv., 2020)

(untitled) - Komatsu, R.; Ohsawa, T.; Sasabe, H.; Nakao, K.; Hayasaka, Y.; Kido, J. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Serevičius, T.; Skaisgiris, R.; Fiodorova, I.; Steckis, V.; Dodonova, J.; Banevičius, D.; Kazlauskas, K.; Juršėnas, S.; Tumkevičius, S. (Org. Electron., 2020)

(untitled) - Serevičius, T.; Skaisgiris, R.; Fiodorova, I.; Kreiza, G.; Banevičius, D.; Kazlauskas, K.; Tumkevičius, S.; Juršėnas, S. (J. Mater. Chem. C, 2021)

(untitled) - Tsiko, U.; Bezvikonnyi, O.; Sych, G.; Keruckienė, R.; Volyniuk, D.; Simokaitienė, J.; Danyliv, I.; Danyliv, Y.; Bučinskas, A.; Tan, X.; Gražulevičius, J. V. (J. Adv. Res., 2021)

(untitled) - Li, S.-W.; Yu, C.-H.; Ko, C.-L.; Chatterjee, T.; Hung, W.-Y.; Wong, K.-T. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Rodella, F.; Saxena, R.; Bagnich, S.; Banevičius, D.; Kreiza, G.; Athanasopoulos, S.; Juršėnas, S.; Kazlauskas, K.; Köhler, A.; Strohriegl, P. (J. Mater. Chem. C, 2021)

(untitled) - Itami, K.; Yamazaki, D.; Yoshida, J.-i. (J. Am. Chem. Soc., 2004)

(untitled) - Maddess, M. L.; Carter, R. (Synthesis, 2012)

(untitled) - Urbonas, R. V.; Poskus, V.; Bucevicius, J.; Dodonova, J.; Tumkevicius, S. (Synlett, 2013)

(untitled) - Kusturin, C.; Liebeskind, L. S.; Rahman, H.; Sample, K.; Schweitzer, B.; Srogl, J.; Neumann, W. L. (Org. Lett., 2003)

(untitled) - Prieur, V.; Pujol, M. D.; Guillaumet, G. (Eur. J. Org. Chem., 2015)

(untitled) - Belaroussi, R.; Ejjoummany, A.; El Hakmaoui, A.; Akssira, M.; Guillaumet, G.; Routier, S. (RSC Adv., 2018)

(untitled) - Jakubkienė, V.; Vaičiūnaitė, E.; Kriukaitė, K.; Didžgalvis, J.; Tumkevičius, S. (Synth. Commun., 2018)

(untitled) - Serevičius, T.; Skaisgiris, R.; Gudeika, D.; Kazlauskas, K.; Juršėnas, S. (Phys. Chem. Chem. Phys., 2022)

(untitled) - Serevičius, T.; Skaisgiris, R.; Dodonova, J.; Jagintavičius, L.; Banevičius, D.; Kazlauskas, K.; Tumkevičius, S.; Juršėnas, S. (ACS Appl. Mater. Interfaces, 2020)

(untitled) - Li, Z.; Li, W.; Keum, C.; Archer, E.; Zhao, B.; Slawin, A. M. Z.; Huang, W.; Gather, M. C.; Samuel, I. D. W.; Zysman-Colman, E. (J. Phys. Chem. C, 2019)

(untitled) - Chan, C.-Y.; Cui, L.-S.; Kim, J. U.; Nakanotani, H.; Adachi, C. (Adv. Funct. Mater., 2018)

(untitled) - Northey, T.; Stacey, J.; Penfold, T. J. (J. Mater. Chem. C, 2017)

(untitled) - Stavrou, K.; Franca, L. G.; Monkman, A. P. (ACS Appl. Electron. Mater., 2020)

(untitled) - Woo, S.-J.; Kim, Y.-H.; Kim, J.-J. (Chem. Mater., 2021)

(untitled) - Etherington, M. K.; Gibson, J.; Higginbotham, H. F.; Penfold, T. J.; Monkman, A. P. (Nat. Commun., 2016)

(untitled) - de Mello, J. C.; Wittmann, H. F.; Friend, R. H. (Adv. Mater. (Weinheim, Ger.), 1997)

(untitled) - Serevičius, T.; Skaisgiris, R.; Kreiza, G.; Dodonova, J.; Kazlauskas, K.; Orentas, E.; Tumkevičius, S.; Juršėnas, S. (J. Phys. Chem. A, 2021)

(untitled) - Rothe, C.; Monkman, A. P. (Phys. Rev. B, 2003)

Gaussian 09 (Gaussian Inc., 2004)

(untitled) - Chen, X.-K. (CCS Chem., 2020)

(untitled) - Yang, Z.; Huang, Y.-B.; Guo, Q.-X.; Fu, Y. (Chem. Commun., 2013)